Role of serum cardiac Troponin-I for risk stratification in first attack in acute myocardial infarction (Bangladesh Journal of Medical Science, 2009)
Introduction: Cardiac troponin-I (cTnI) is known to have the highest specificity and analytic sensitivity for detection of myocardial injury; it is used both as diagnostic and prognostic marker. This study was aimed to confirm this idea. Subjects & methods: This prospective observational study included 60 patients of 40 to 65 years age range diagnosed as acute myocardial infarction. The mean ages were 50±8 years and 53±8 years in Q -wave AMI and non Q-wave AMI respectively. Male and female patients included were 86.7% and 13.3%; BMI was 25.3±1.5. Results: Study showed troponin-I 7.53±0.086 ng/ml in Q wave and in non Q-wave AMI was 6.38±0.64 ng/ml after 24 hours of attack of AMI without any significant difference between two groups (P>0.05). The mean troponin-I within 9 hours of attack, were 1.60±0.80 ng/ml and 2.7±1.4 ng/ml in stable and unstable group respectively and the difference found statistically significant (P1.5 ng/ml in which 29 patients developed unstability and 8 patients were stable. Conclusion: Serum cTnI is better and more characteristic biomarker for risk prediction and prognosis evaluation in AMI patients. Key words: Cardiac Troponin-I, acute myocardial infarction, risk stratification.   DOI: 10.3329/bjms.v8i3.3984 Bangladesh Journal of Medical Sciences Vol.8(3) 2009 p57-63